The availability of Professional Responsibility Standards for Shari Sciences Teachers in Secondary Stage in Kharj City - Al-Dawood, Hamad Fawaz (Journal of Humanities & Social Sciences, 2018)
This research aimed to Identify the availability of professional responsibility standards for Shari sciences teachers in secondary stage in Kharj city from the perspective of teachers. To achieve the study objectives، the researcher used the descriptive (survey) method، and did interviews as tool of the study. The study comprised 3 main standards، 8 sub-standards، 46 indicators. The study was applied to (75) sharia sciences teachers in secondary stage and (23) principals of high schools in Kharj district. The most Important findings of the research: 1- The degree of professional responsibility for sharia sciences teachers in secondary stage in Kharj city from the perspective of teachers was (intermediate) in general، excluding the degree of third main standard (Saudi Teachers’ awareness of professional skills) was high. 2- The degree of professional responsibility for sharia sciences teachers in secondary stage in Kharj district from the perspective of principals was (intermediate) in general، excluding the degree of third main standard (Saudi Teachers’ awareness of professional skills) was high. 3- The absence of statistically significant differences in the degree of availability of professional responsibility standards for sharia teachers in secondary stage in Kharj city due to academic degree of teaching experience.